Morphological and Growth Properties of Albino Rat Bone Marrow Stromal Cells In Vitro - Mnati, I. M.; Mutlak, B.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The potential use of bone marrow stromal cells as a cellular therapy for chronic diseases relies on the ability of the cell to replicate extensively in vitro.For this reason the present study investigated the replication lifespan and examined the growth properties of albino rats mesenchymal stem cells(MSCS)in vitro. To establish an in vitro system for isolating and culturing the  MSCs of albino rats and to provide research data for its further application,the bone marrow (BM)was collected from young male rats and separated by gradient centrifugation.Then, the mononuclear cells(MNCs) were retrieved from the buffy layer and cultured in Modified Eagle,s Medium (MEM) supplemented with 10%Fetal Calf Serum (FCS)and incubation at 37Co in humid air with 5%CO2 .  The non-MSCs were screened out.A passage culture was undertaken while the monolayer of adherent cells formed .The spindle â€“shaped MSCS with a single nucleus formed a monolayer after the 10-12 days of primary culturing,and the cells appeared in an oriented array with a swirling growth trend.  In the anaphase of passage culture ,the cell proliferation rate was decreased and the morphology changed into broad flat appearance.These results suggested that MSCS of the albino rats can be passaged in vitro with the established optimized culture system,in addition, the growth curves can be divided into three phases:the initial quiescent phase,the logarithmic replication phase and after logarithmic  replication phase